A reappraisal of the value of video-EEG recording in the emergency department. (3rd May 2020) - Raucci, Umberto; Pro, Stefano; Di Capua, Matteo; Di Nardo, Giovanni; Villa, Maria Pia; Striano, Pasquale; Parisi, Pasquale
ABSTRACT: Introduction : Some neurologic conditions that can quickly and with low costs be recognized, classified and treated thanks to the availability of an EEG recording in an emergency setting. However, although considered a cheap, not invasive, highly accurate diagnostic investigation, still today, an EEG recording in emergency, in real time during the event paroxysmal ictal phase, is not yet been become a routine. Areas covered : This review will cover the role and utility of EEG recording in the emergency setting, both in emergency department and intensive care unit, in adult and pediatric age, in people admitted for status epilepticus (convulsive or non-convulsive), paroxysmal non-epileptic events, or other conditions/diseases presenting with mental status changes. Expert opinion : The prompt recognition of some specific EEG-patterns can permit an immediate and appropriate therapeutic choice with the resolution of dramatic clinical pictures, which, if not recognized, sometimes could result in severe prognostic events with high mortality or neuropsychiatric disability. It is important in the next future, to improve the availability of these EEG digital continuous monitoring, which should be widely used in emergency settings, developing moreover tools and techniques permitting also review, analysis and EEG-reporting by experts who can work away from the hospital.